Scattering problem for a multidimensional system of first-order partial differential equations - Nizhnik, L. P.; Tarasov, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We construct transformation operators, which enables us to study a scattering problem and investigate the properties of a scattering operator for a multidimensional system of first-order partial differential equations.